2011
DOI: 10.1021/ie101999p
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sodium Borohydride on Kraft Pulping of European Black Pine as a Digester Additive

Abstract: In this study, the effects of sodium borohydride (NaBH4) on properties of kraft pulp and paper obtained from European black pine (Pinus nigra Arn.) were investigated. Kraft−NaBH4 cookings were done under fixed cooking conditions by adding NaBH4 in the amounts of 0.5%, 1%, 1.5%, and 2% (oven-dried wood) to the cooking liquor. NaBH4-free kraft cooking was carried out as control. The results indicated that addition of NaBH4 to cooking liquor increased the pulp yield. However, the kappa number of pulp and beating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 5 publications
1
15
0
1
Order By: Relevance
“…The increase of the beating degree from 15 °SR (CS‐free) to 20, 25, and 30 °SR led to increments in the tensile index of 150, 218, and 236%, respectively. Similar results have been reported in other studies . This rise in the tensile index could be ascribed to the increase in the bonded area of the fibers owing to the internal and external fibrillation that occurs during beating .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The increase of the beating degree from 15 °SR (CS‐free) to 20, 25, and 30 °SR led to increments in the tensile index of 150, 218, and 236%, respectively. Similar results have been reported in other studies . This rise in the tensile index could be ascribed to the increase in the bonded area of the fibers owing to the internal and external fibrillation that occurs during beating .…”
Section: Resultssupporting
confidence: 91%
“…The increase of the pulp beating degree from 15°SR to 20, 25, and 30°SR increased the burst index by 100, 122, and 129%, respectively. Several investigations reported that beating results in an increase in the burst index [21,32]. However, addition of 0.75, 1.5, and 2.25% CS to the 15°SR pulp increased the burst index as 177%, 262%, and 278%, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Yield-increasing additives to stabilise glucomannan (Rydholm 1965) can be either reducing or oxidizing chemicals. A reducing additive is sodium borohydride (NaBH 4 ), which yields stable alcohol groups (Rydholm 1965;Gulsoy, Eroglu 2011) and sodium borate according to the reaction (Rydholm 1965), Eq 1. 4RCHO+NaBH 4 +2NaOH+H 2 O 4RCH 2 OH+Na 3 BO 3 [1] At the same time a side reaction occurs, Eq 2.…”
Section: Introductionmentioning
confidence: 99%
“…4RCHO+NaBH 4 +2NaOH+H 2 O 4RCH 2 OH+Na 3 BO 3 [1] At the same time a side reaction occurs, Eq 2. NaBH 4 +2NaOH+H 2 O 4H 2 +Na 3 BO 3 [2] The most important advantage of using NaBH 4 is the significant yield increase, but there are other advantages such as energy savings during refining and an increase in pulp brightness (Gulsoy, Eroglu 2011). An oxidizing chemical additive is polysulfide which can be produced by adding elemental sulfur to white liquor (Rydholm1965; Lindgren, Lindström 1995), when the following reaction takes place already at 70°C, Eq 3.…”
Section: Introductionmentioning
confidence: 99%
“…Higher hemicellulose content results in an increase of pulp strength. Gulsoy and Eroglu (2011) noted that tensile index increased in European black pine kraft pulp, and Gümüşkaya et al, (2011) noted that it increased in stone pine AS-AQ pulp with NaBH 4 addition. On the contrary, some authors noted that NaBH 4 had a negative effect on tensile index of handsheets (Akgül et al, 2007;Çöpür ve Tozluoğlu, 2008;Istek and Özkan, 2008).…”
Section: Drvna Industrijamentioning
confidence: 99%